2008
DOI: 10.1029/2008gl035393
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and optimality of the water budget on land: A review

Abstract: [1] The water balance on land plays a critical role in connecting key hydrological processes with climate and ecology. Over the last few years, several advances have been made in applying thermodynamic and optimality approaches to better describe Earth system processes in general, and the water balance on land in particular. Both concepts relate to the proposed principle of Maximum Entropy Production (MEP), which states that complex systems far from thermodynamic equilibrium organize in a way such that the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
134
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(136 citation statements)
references
References 42 publications
1
134
1
Order By: Relevance
“…Soil water potential µ soil is formulated as the sum of the modified matric potential M and the gravitational potential of water in the soil (Kleidon and Schymanski, 2008). In general, both potentials vary with the height z of the soil water:…”
Section: The Potential Of Water In Different Parts Of the Hydrologicamentioning
confidence: 99%
See 2 more Smart Citations
“…Soil water potential µ soil is formulated as the sum of the modified matric potential M and the gravitational potential of water in the soil (Kleidon and Schymanski, 2008). In general, both potentials vary with the height z of the soil water:…”
Section: The Potential Of Water In Different Parts Of the Hydrologicamentioning
confidence: 99%
“…The potential of water vapour in the atmospheric boundary layer is written as (Kleidon and Schymanski, 2008):…”
Section: The Potential Of Water In Different Parts Of the Hydrologicamentioning
confidence: 99%
See 1 more Smart Citation
“…Juretic and Zupanovic [2003] found that the MEP may govern the photosynthetic processes. Evidence accumulated so far suggests that the MEP theory could explain transport phenomena in the far from equilibrium systems over a wide range of space and time scales [Kleidon and Schymanski, 2008]. We intend to show that the MEP not only explains the observed behavior of nonequilibrium thermodynamic processes, but also can provide a predictive tool in modeling the transport processes quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…The MEP principle has recently gained increased attention (e.g. recent reviews by Ozawa et al (2003), Martyushev & Seleznev (2006), Kleidon & Schymanski (2008) and Kleidon (2009b) and the book by Kleidon & Lorenz (2005)), but has mostly been applied to purely physical processes within the Earth system, such as turbulence in the atmosphere (e.g. Paltridge 1975Paltridge , 1978Grassl 1981;Lorenz et al 2001;Kleidon et al 2003).…”
Section: Introductionmentioning
confidence: 99%